A Comparison of the Functional Independence Measure and Morse Fall Scale as Tools to Assess Risk of Fall on An Inpatient Rehabilitation. Issue 4 (29th May 2013) - Forrest, George P.; Chen, Eric; Huss, Sara; Giesler, Andrew
Abstract Purpose The purpose of this study was to determine if the Functional Independence Measure (FIM) is as useful as the Morse Fall Scale in determining which patients admitted to an inpatient rehabilitation facility (IRF) are at highest risk for fall. Method Review of the charts of all patients admitted to an IRF in calendar year 2010. Findings Low scores on the FIM are as useful as high scores on the MFS in suggesting that a patient is at high risk for fall. Conclusions and Clinical Relevance Nursing staffs that use the FIM to comply with Centers for Medicare and Medicaid Services (CMS) documentation requirements likely do not benefit by also evaluating and documenting the patients' score on the MFS.